Overeducation, Regional Labour Markets and Spatial Flexibility - Felix Büchel; Maarten van Ham (Institute for the Study of Labor (IZA), 2002)
For most workers, access to suitable employment is severely restricted by the fact that they look for jobs in the regional labour market rather than the global one. In this paper we analyse how macro-level opportunities (regional labour market characteristics) and microlevel restrictions (the extent to which job searchers are restricted to the regional labour market) can help to explain the phenomenon of overeducation. For the purposes of this project we obtained special permission to link regional data supplied by the German Federal Office for Building and Regional Planning to data provided by the respondents in the German Socio-Economic Panel (GSOEP), based on their region of residence. The use of multilevel models made it possible to combine both individual and regional characteristics in the same models. In addition, we used the Heckman two-step procedure to control for selective access to employment. The results show that the size of the labour market is an important factor in avoiding overeducation: looking for a job on a large labour market increases the probability of finding a suitable job. Access to a car for personal use and a longer commuting time reduce the risk of working in a job for which one is overeducated.
Keywords: J24; J44; J62; J61; I21; 330; Overeducation; regional labour markets; spatial flexibility; multilevel models; Arbeitsangebot; Überqualifikation; Regionaler Arbeitsmarkt; Regionale Arbeitsmobilität; Schätzung; Deutschland